COMPARISION BETWEEN BED SIDE TESTING OF BLOOD GLUCOSE BY GLUCOMETER Vs CENTRALIZED TESTING IN A TERTIARY CARE HOSPITAL - Baig, Ayaz; Siddiqui, Imran; Jabbar, Abdul; Azam, Syed Iqbal; Sabir, Salman; Alam, Shahryar; Ghani, Farooq (Journal of Ayub Medical College Abbottabad, 2007)
Background: To determine the accuracy, turnaround time and cost effectiveness of bedside monitoring of blood glucose levels by non-laboratory health care workers and centralized testing of blood glucose by automated analyzer in a tertiary care hospital. Methods: The study was conducted in Section of Chemical Pathology, Department of Pathology and Microbiology and Section of Endocrinology Department of Medicine, Aga Khan University and Hospital Karachi, from April 2005 to March 2006.One hundred and ten patients were included in the study. The blood glucose levels were analyzed on glucometer (Precision Abbott) by finger stick, using Biosensor Technology. At the same time venous blood was obtained to analyze glucose in clinical laboratory on automated analyzer (SYNCHRON CX7) by glucose oxidase method. Results: We observed good correlation between bed side glucometer and laboratory automated analyzer for glucose values between 3.3 mmol/L (60 mg/dl) and 16.7 (300 mg/dl). A significant difference was observed for glucose values less than 3.3 mmol/L (p=0.002) and glucose values more than 16.67 mmol/l (p= 0.049). Mean Turnaround time for glucometer and automated analyzer were 0.08 hours and 2.49 hours respectively. The cost of glucose testing with glucometer was 48.8% lower than centralized lab based testing. Conclusion: Bedside glucometer testing, though less expensive does not have good accuracy in acutely ill patient with either very high or very low blood glucose levels. Key words: Bed side testing; Glucometer; Centralized glucose testing